2011
DOI: 10.1073/pnas.1113107108
|View full text |Cite
|
Sign up to set email alerts
|

E339…R416 salt bridge of nucleoprotein as a feasible target for influenza virus inhibitors

Abstract: The nucleoprotein (NP) of the influenza virus exists as trimers, and its tail-loop binding pocket has been suggested as a potential target for antiinfluenza therapeutics. The possibility of NP as a drug target was validated by the recent reports that nucleozin and its analogs can inhibit viral replication by inducing aggregation of NP trimers. However, these inhibitors were identified by random screening, and the binding site and inhibition mechanism are unclear. We report a rational approach to target influen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
110
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(118 citation statements)
references
References 22 publications
6
110
0
Order By: Relevance
“…In this report, N245-382 and N245-389 show a very high degree of stability compared to the other C-terminal domain truncations of the HCoV-229E N protein due to a high degree of subunit interactions. The inhibition of viral N protein oligomerization by developing competing peptides and small organic compounds is an attractive therapeutic strategy against viral infection [53][54][55]. We showed that a peptide based on the C-terminal tail interfered with the oligomerization of the C-terminal domain of the HCoV-229E N protein, N245-389 and performed the inhibitory effect on viral titre of HCoV-229E.…”
Section: Discussionmentioning
confidence: 99%
“…In this report, N245-382 and N245-389 show a very high degree of stability compared to the other C-terminal domain truncations of the HCoV-229E N protein due to a high degree of subunit interactions. The inhibition of viral N protein oligomerization by developing competing peptides and small organic compounds is an attractive therapeutic strategy against viral infection [53][54][55]. We showed that a peptide based on the C-terminal tail interfered with the oligomerization of the C-terminal domain of the HCoV-229E N protein, N245-389 and performed the inhibitory effect on viral titre of HCoV-229E.…”
Section: Discussionmentioning
confidence: 99%
“…The identification of ligands which prevent the formation of the salt bridge will be of particular interest to combat both types of influenza viruses. Intriguingly, an inhibitor which targets the salt bridge of ANP has been recently identified (28). It will be interesting to find out whether this inhibitor also targets the BNP salt bridge.…”
Section: Discussionmentioning
confidence: 99%
“…The swapping loop, important for the stabilization of the trimeric interface, was considered to be a good target for the design of new NPdirected antivirals based on structural studies (4,5). Indeed, the salt bridge between E339 and R416 from neighbor monomers required for NP trimerization was targeted by NP inhibitors identified by virtual screening (16). Other compounds targeting cellular proteins involved in the nuclear transport of the RNP or in signaling pathways exploited by influenza A virus also exhibited antiviral effects (17,18).…”
mentioning
confidence: 99%